Blistering and Skin Fragility Due to Imatinib Therapy: Loss of Laminin and Collagen IV as a Possible Cause of Cutaneous Basement Membrane Instability. (May 2018) - Mühl, Sebastian; Ehrchen, Jan; Metze, Dieter
Abstract : Abstract: Imatinib mesylate (Glivec; Novartis AG, Basel, Switzerland) is a tyrosine kinase inhibitor which is used in the treatment of oncologic diseases like chronic myeloid leukemia and gastrointestinal stroma tumor (GIST). Among cutaneous side effects, bullous reactions are rare. The authors describe the case of a 66-year-old woman developing blistering and skin fragility on her hands, foot, lower legs, and back after intake of imatinib for treatment of GIST. Biopsy showed vacuolar alteration at the dermoepidermal junction (DEJ) associated with a few lymphocytes and a subepidermal blister. The upper papillary dermis below the vacuolar alteration and below the blister showed hyalinization and loss of elastic microfibrils. Direct immunofluorescence was negative for deposits of immunoglobulins. Immunofluorescence on cryosections revealed loss of laminin and collagen IV in vacuoles at the DEJ. Electron microscopy showed dissolution of lamina lucida and lamina densa of the basement membrane below as well as next to the vacuoles and blister. In conclusion, the authors present the first patient with GIST with blistering and skin fragility due to imatinib therapy. As a pathophysiological explanation the authors propose loss of laminin and collagen IV at the DEJ leading to basement membrane instability and blistering. This case also suggests additional features reminiscent of lichen sclerosus induced by imatinib, a drug which is actually known for its antifibrotic effects.